2014
DOI: 10.1038/ismej.2014.186
|View full text |Cite
|
Sign up to set email alerts
|

A novel cohabitation between two diazotrophic cyanobacteria in the oligotrophic ocean

Abstract: The cyanobacterial genus Trichodesmium is biogeochemically significant because of its dual role in nitrogen and carbon fixation in the oligotrophic ocean. Trichodesmium species form colonies that can be easily enriched from the water column and used for shipboard rate measurements to estimate their contribution to oceanic carbon and nitrogen budgets. During a July 2010 cruise near the Hawaiian Islands in the oligotrophic North Pacific Subtropical Gyre, a specific morphology of Trichodesmium puff-form colonies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 74 publications
1
35
0
1
Order By: Relevance
“…These associations warrant further scrutiny, but were a small component of the total observations. A recent study near Station ALOHA, in the North Pacific, reported high numbers of Calothrix-like heterocystous cyanobionts in 75% of the Trichodesmium puff colonies (Momper et al, 2015). This association with a cyanobiont that fixes nitrogen with a temporal offset to Trichodesmium could influence colony derived nitrogen-fixation budgets depending on its prevalence and distribution (Momper et al, 2015).…”
Section: Epibiont Diversity Of the Trichodesmium Holobiontmentioning
confidence: 99%
See 1 more Smart Citation
“…These associations warrant further scrutiny, but were a small component of the total observations. A recent study near Station ALOHA, in the North Pacific, reported high numbers of Calothrix-like heterocystous cyanobionts in 75% of the Trichodesmium puff colonies (Momper et al, 2015). This association with a cyanobiont that fixes nitrogen with a temporal offset to Trichodesmium could influence colony derived nitrogen-fixation budgets depending on its prevalence and distribution (Momper et al, 2015).…”
Section: Epibiont Diversity Of the Trichodesmium Holobiontmentioning
confidence: 99%
“…Within the colony, Trichodesmium are only a member of a complex holobiont, a host-microbiome system, where Trichodesmium filaments host high concentrations of tightly attached heterotrophic bacterial epibionts (Herbst and Overbeck, 1978;Paerl et al, 1989;Zehr, 1995;Dyhrman et al, 2002;Hewson et al, 2009). In addition, other cyanobacteria have been observed in association with Trichodesmium colonies (Hewson et al, 2009;Hynes et al, 2009;Hmelo et al, 2012;Momper et al, 2015). Studies have suggested that the metabolism of Trichodesmium and heterotrophic bacterial epibionts is tightly interconnected and that epibionts might play an important role in the cycling of iron and phosphorus within the colony (Achilles et al, 2003;Roe et al, 2012;Van Mooy et al, 2012), with concomitant impacts on ocean biogeochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Whole genomic DNA was extracted using a modified phenolchloroform extraction with ethanol precipitation. In brief, this included three rounds of physical (freeze, thaw, vortex) and chemical (lysozyme) disruption of the cell wall prior to phenol-chloroform extraction according to Momper et al (2015). Controls during DNA extraction and polymerase chain reaction (PCR) confirmed that there were no contaminating nucleic acids during the extraction process (data not shown).…”
Section: Dna Collection Extraction and Sequencingmentioning
confidence: 99%
“…If we adjusted our heterocyst counts by a factor of 5 to include gene copies in vegetative cells, qPCR based abundance are on average more than a 100 × higher than cell-based estimates. Other potential explanations for this disparity include (1) the potential for nonspecificity of het-1 and het-2 primers and probes as described in Foster et al (2007), (2) omission of heterocysts that may have been embedded in Trichodesmium colonies and hence not readily visible via microscopy (Momper et al, 2015), and (3) amplification of moribund DNA that would not have been detected by epifluorescence microscopy. The lack of agreement between gene and cell based abundances is a topic that clearly needs further study.…”
Section: Month-yearmentioning
confidence: 99%